How Does Changing Pesticide Usage Over Time Affect Migrating Amphibians: A Case Study on the Use of Glyphosate-Based Herbicides in German Agriculture Over 20 Years - Berger, Gert; Graef, Frieder; Pallut, Bernhard; Hoffmann, Jörg; Brühl, Carsten A.; Wagner, Norman (Frontiers in Environmental Science, 2018)
Since its introduction in 1974, the use of glyphosate in agriculture has been continuously increasing; however, the application modes of this herbicide have been changing. Therefore, glyphosate-based herbicides can be used as an appropriate indicator for assessing how changes in pesticide application modes affect wild-living organisms in agricultural landscapes over time. Amphibians that migrate through arable fields may be exposed to the chemicals applied to field crops. Using data on the tem-poral coincidence of four amphibian populations with glyphosate applications from a three-year in-vestigation in northeast Germany as well as data on the application of glyphosate to field crops in German agriculture over 20 years, we estimated the species-specific increasing rates of coincidence likelihoods during this period. The overall consumption of glyphosate used in German agriculture between 1992 and 2012 increased by a factor of 5.7, while the species-specific coincidence likelihood increased from 2.2 to 6.1, respectively. Our results reveal the highest increases in coincidence for both adult and juvenile great crested newt (Triturus cristatus) and fire-bellied toad (Bombina bombina). Adults and juveniles of moor frog (Rana arvalis) and adults of spadefoot toad (Pelobates fuscus) were subjected to moderate increases, with rates ranging from 3.2 to 3.6; in contrast, juvenile individuals of P. fuscus showed small increases. We suggest that the risk assessments of pesticide application (in this case, glyphosate) should not only consider the present use at the time of authorization but also consider changes in application modes over time that may lead to increases in potential exposure of non-target organisms, such as amphibians.